A Review of Mathematical Programming in Integrated Iron‐ and Steelmaking. Issue 10 (6th August 2018) - van Beek, Mathias
Abstract: This paper presents and reviews the current application fields of mathematical programming in integrated iron‐ and steelmaking research. Three different fields of mathematical programming applications are identified and discussed: unit operation optimization, by‐product gas distribution, and integrated system optimization and design. Based on current research activities in the iron and steel industry, development trends for mathematical programming in integrated iron‐ and steelmaking research, such as the cogeneration of chemicals aided by renewable energy grid integration, are presented. Abstract : Mathematical programming has emerged as a popular research method in integrated iron‐ and steelmaking with application fields such as by‐product gas distribution. This article reviews recent developments in mathematical programming applications and identifies future research areas for the method in the iron‐ and steelmaking context.